On the issue of intensification and the choice of intensifier - Polishchuk, O. S. (НУБіП України, 2019)
One of the main issues, which relates to the study of the category of intensity and draws much attention of linguists is the exact description of its position among other semantic categories, the definition of its boundaries, interconnection and interaction. The subject of this work is the semantic category of intensity, which is inherent, at least indirectly, in principle in any linguistic situation, and which can be embodied in the language in a variety of ways. The most interesting is the level of phraseology, because stable comparative phrases capture traditional national images and representations preserved from the earliest times, and allow demonstrating the specificity and relevance of the symbols of individual nations. The purpose of this study is, firstly, to analyse the essence and limits of the semantic category of intensity, its position and relationship with other linguistic categories; and secondly, to review of the means of expressing this category on the appropriate language levels; and, thirdly, on the background of the linguistic corps, to compare Russian and English stable comparative phrases.
До проблеми інтенсифікації та вибору інтенсифікатора
Одним з основних питань, що відносяться до вивчення категорії інтенсивності і звертають на себе велику увагу лінгвістів, є точний опис її позиції серед інших семантичних категорій, визначення їх меж, взаємозв'язку і взаємодії. Предметом даної роботи є семантична категорія інтенсивності, яка властива, принаймні, побічно, в принципі будь-якій мовній ситуації, і яка здатна утілюватися в мові найрізноманітнішими способами. З особливим інтересом вивчається рівень фразеологізму, зокрема стійкі порівняльні звороти, оскільки (не лише) за допомогою їх зафіксувалися традиційні національні образи і уявлення, що збереглися з найдревніших часів, і саме на прикладі стійких порівнянь можна виразно продемонструвати специфіку і відповідності в символіці окремих народів. Метою цієї роботи є, по-перше, аналіз суті і меж семантичної категорії інтенсивності, її позицію і взаємовідносини з іншими близькими категоріями; по-друге, проведення структурованого огляду засобів вираження цієї категорії на відповідних мовних рівнях; і, по-третє, на тлі лінгвістичного корпусу зображувати зіставлення російських і англійських стійких порівняльних зворотів.
Keywords: intensification; intensity; intensifier gradation; gradualism; sign; trait; інтенсифікація; інтенсивність; інтенсифікувальна гра дуальність; градація; ознака